In-situ Raman spectroscopic analysis of phase transition temperatures in silica interacting with water and NaCl solutions - Krishnakumari Pamula; Amol Pophali; Dilip Gersappe; Taejin Kim (Scientific Reports)
Abstract Phase transition temperatures of pure water and aqueous sodium chloride (NaCl) solutions, both in bulk form and mixed with the silica (SiO2) powder, were investigated using in-situ Raman spectroscopy. To determine the freezing and melting temperatures, the OH-stretching and bending regions of the Raman spectrum were analysed, along with investigation of hydrohalite (HH) formation in saline water. A spectral phase transition marker, SD, defined as the intensity ratio of asymmetric to symmetric OH-stretching bands (Iasym/Isym), was applied to measure the freezing and melting temperatures. In the case of bulk water and aqueous salt solutions, complete tranformation of liquid to solid phase was noticed. However, in the case of SiO2 mixed liquids, a non-freezable liquid layer was observed, which could be due to the interaction between the silanol (Si–OH) functional groups and the water/NaCl solution. These findings are expected to provide valuable insights into the freezing and thawing processes in both normal and saline soil in cold regions.